2021
DOI: 10.37908/mkutbd.940809
|View full text |Cite
|
Sign up to set email alerts
|

Hatay ili Arsuz ilçesi topraklarının besin elementi durumları ve bunların bazı toprak özellikleri ile ilişkileri

Abstract: It was aimed to determine some the macro and micro nutrient concentration of the soils of Arsuz district of Hatay province and to evaluate the fertility status of the soils of the region by revealing their relationship with some soil properties. Methods and Results:In the study, a total of 70 surface soil samples were taken from a depth of 0-30 cm and 70 different points, representing the lands of Hatay-Arsuz district. According to the results of the research, total N concentration of soils were determined bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It is reported that with the increase of OM and decrease in pH, the exchange of K, a base cation with high absorbance in soil, increases and it can be found in forms that can be taken by the plant (Siregar et al, 2005;Whittinghill and Hobbie, 2012). Many studies have stated that OM in the soil increases the exchangeable K activation (Khoshgoftarmanesh and Kalbasi, 2002;Verma et al, 2005;Yalçın et al, 2018;Çimrin, 2020). The effect of organomineral fertilizers applied during the study period on the exchangeable Na content of the soil was not statistically significant.…”
Section: Organomineral Phosphorus Fertilization Systemmentioning
confidence: 99%
“…It is reported that with the increase of OM and decrease in pH, the exchange of K, a base cation with high absorbance in soil, increases and it can be found in forms that can be taken by the plant (Siregar et al, 2005;Whittinghill and Hobbie, 2012). Many studies have stated that OM in the soil increases the exchangeable K activation (Khoshgoftarmanesh and Kalbasi, 2002;Verma et al, 2005;Yalçın et al, 2018;Çimrin, 2020). The effect of organomineral fertilizers applied during the study period on the exchangeable Na content of the soil was not statistically significant.…”
Section: Organomineral Phosphorus Fertilization Systemmentioning
confidence: 99%